Optimization of the ratio of aniline, ammonium persulfate, para-toluenesulfonic acid for the synthesis of conducting polyaniline and its use in energy storage devices - Das T.; Pandey V.K.; Verma S.; Pandey S.K.; Verma B. (My University, 2025)
We have successfully synthesized para-toluenesulfonic acid (PTSA)-based conducting polyaniline (PA) by using ammonium persulfate (APS) as oxidant for supercapacitor electrode applications. The primary aim is to find out the optimized ratio of APS:aniline and aniline:PTSA based on the electrochemical performances of the fabricated electrodes. PA having APS:aniline ratio of 1.25:1 and aniline:PTSA ratio of 2:1 exhibited the highest value of specific capacitance, specific energy, specific power, and coulombic efficiency of 82.22 F/g, 11.42 Wh/kg, 124.99 W/kg, and 95.95%, respectively. It offers very low charge transfer resistance of 3.1 Ω during the electrochemical processes. The cycle life of the corresponding system is the largest among all, which is 88.97% retention after 2000 cycles. The robust electrochemical behavior may be due to the uniform rod-shaped morphology of the corresponding system, which may be providing seamless movement of the electrolyte ions to the electrochemical active sites along with proper electrical connection. © 2022 John Wiley & Sons Ltd.